PELAKSANAAN TUGAS DAN FUNGSI DINAS TENAGA KERJA KOTA PEKANBARU DI KOTA PEKANBARU TAHUN 2017-2018 - Vincentius Andy Candra Sinaga; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In carrying out the main tasks and functions of the Pekanbaru City Manpower Office based on the Pekanbaru City Regulation No. 8 of 20018 concerning the Formation of Organizational Structure, Position, and Main Duties of Offices in the Pekanbaru City Government Environment, the Pekanbaru City Manpower Office has duties and functions, one of which is an increase in the quality of skilled, productive and independent human resources in creating jobs and being able to meet the needs of work and the world of work.As for the Problems Formulation in this study, namely: First, How the Implementation of Duties and Functions of the City of Pekanbaru Manpower Office in Pekanbaru City in 2017-2018. Second, What are the factors faced by the Office of Manpower in Carrying Out its Tasks and Functions in Reducing the Unemployment Level in Pekanbaru City in 2017-2018. Reducing Unemployment in Pekanbaru City in 2017-2018. Second, to find out what are the factors faced by the Office of Manpower in Carrying Out its Tasks and Functions to Reduce Unemployment in Pekanbaru City in 2017-2018. This research is a qualitative research. This research was conducted at the Pekanbaru City Manpower Department. The techniques used to collect data in this study are (1) Interviews, (2) Observation, and (3) Documentation.The conclusion of this research shows that the implementation of the duties and functions of the Pekanbaru City Manpower Office in Reducing the Unemployment Rate in Pekanbaru City has been running optimally. With proven programs implemented such as successful programs that have been implemented such as the job expo program and job fair ... Pekanbaru City Manpower Office to reduce the unemployment rate in Pekanbaru City and the low interest in filling vacancies outside the region. The author suggests that the Pekanbaru City Manpower Office should improve its performance in overcoming the problem of unemployment on a regular basis to improve the quality of job seekers through the improvement of certified education and research. Keywords: Pekanbaru City Manpower Office, Unemployment.